Simultaneous measurement of methylamine in size-segregated aerosols and the gas phase. Issue 1 (1st January 2021) - Hirai, Aki; Matsumoto, Kiyoshi
Abstract: In order to improve our understanding of the origin and production processes of methylamine in the atmosphere and its contribution to the particulate WSON, simultaneous measurements of methylamine in size-segregated aerosols and the gas phase were conducted at a forested site in Yamanashi Prefecture, Japan, over one year. The concentration of the atmospheric methylamine that is the sum of methylamine in the gas phase, coarse-mode, and fine-mode particles was 0.962 ng-N m −3 on average. About 77% of the atmospheric methylamine was detected in the fine-mode particles and about 17% was in the gas phase. Similar seasonal variations were found in the fine-mode and gaseous methylamine including higher concentrations recorded in summer. The relationship between the concentrations of the gaseous methylamine and ammonia showed a significant positive correlation, suggesting that methylamine in the gas phase has similar sources with ammonia; for instance, the volatilization from soil and/or emission from forest biological activities. The concentration of the fine-mode methylamine showed a significant positive correlation with that of the gaseous methylamine, and the concentration ratio of the fine-mode methylamine to the sum of the fine-mode and gaseous methylamine that can be an indicator of the conversion of methylamine from the gas phase to the particulate phase showed a significant positive correlation with the fine-mode non-sea salt SO4 2- (nss-SO4 2- ) concentration, suggesting that the gaseous methylamine is converted into the particulate methylamine through the acid-base reaction with sulfuric acid and/or nss-SO4 2- . Significant positive correlation was not obtained in the comparison of the concentration ratio of the fine-mode methylamine to the sum of the fine-mode and gaseous methylamine with the excessive amount of sulfuric acid for complete neutralization of ammonia, which implies the possibility that the sulfuric acid more preferentially reacts with the gaseous methylamine than ammonia.